2005
DOI: 10.1037/1064-1297.13.2.111
|View full text |Cite
|
Sign up to set email alerts
|

Transdermal Methylphenidate, Behavioral, and Combined Treatment for Children With ADHD.

Abstract: Stimulant medication and behavioral treatments are evidence-based for children with attention-deficit/hyperactivity disorder, but the combination of the 2 treatments has been understudied. In this investigation, methylphenidate (MPH) was crossed with 2 levels of behavior modification (BMOD) in a summer treatment program. Twenty-seven children with attentiondeficit/hyperactivity disorder, aged 6 -12, participated. Children received placebo and 3 doses of transdermal MPH (12.5 cm 2 , 25.0 cm 2 , and 37.5 cm 2 ).… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
91
1
3

Year Published

2006
2006
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 127 publications
(104 citation statements)
references
References 73 publications
9
91
1
3
Order By: Relevance
“…The SMD between guanfacine extended release and placebo for oppositional behaviour was 0.43 (95% CI 0.18 to 0.68; I 2 = 5 4%, P < 0.001), by 13 Gadow et al 19 Gorman et al 16 Gorman et al 16 Greenhill et al 12 Pelham et al 9 Sinzig et al 14 Wilens et al Table 1. Overall, there is moderate-quality evidence that guanfacine has a small-to-moderate effect on oppositional behaviour in youth with ADHD, with and without ODD.…”
Section: Guanfacinementioning
confidence: 99%
See 1 more Smart Citation
“…The SMD between guanfacine extended release and placebo for oppositional behaviour was 0.43 (95% CI 0.18 to 0.68; I 2 = 5 4%, P < 0.001), by 13 Gadow et al 19 Gorman et al 16 Gorman et al 16 Greenhill et al 12 Pelham et al 9 Sinzig et al 14 Wilens et al Table 1. Overall, there is moderate-quality evidence that guanfacine has a small-to-moderate effect on oppositional behaviour in youth with ADHD, with and without ODD.…”
Section: Guanfacinementioning
confidence: 99%
“…Eleven evaluated methylphenidate [9][10][11][12][13][14][15][16][17][18][19] and 1 studied lisdexamphetamine 20 in children with ADHD. These 12 RCTs included a total of 1681 participants.…”
Section: Study Outcomesmentioning
confidence: 99%
“…8 Although the number of neuropsychological studies of other comorbidities in ADHD is limited, youths with ADHD and anxiety disorders show fewer severe deficits in response inhibition tasks but more severe deficits in working memory tasks than youths with only ADHD. 9 Meta-analyses have not yielded strong evidence of neuropsychological differences between ADHD DSM-IV subtypes 10 ; however, one study 11 documented greater difficulty with resistance to interference in patients with ADHD-Inattentive subtype compared to those with other subtypes.…”
Section: Referencesmentioning
confidence: 99%
“…One study 10 reported high remission rates of tic disorders and an overall limited impact on the course of ADHD. In contrast to the severe consequences of other comorbid disorders such as conduct, mood, and anxiety disorders, tic disorders minimally affect the overall outcome of ADHD.…”
Section: Tic Disordersmentioning
confidence: 99%
See 1 more Smart Citation